Injured Workers Perspectives on Recovery following Non-Life-Threatening Acute Orthopaedic Trauma: A Descriptive Study. (23rd February 2014) - Clay, Fiona J.; Shourie, Swati; Robinson, Priscilla; McKenzie, Donna; Kerr, Emily
Abstract : Background . Little is known about the recovery process following non-life-threatening acute orthopaedic trauma from the viewpoint of the injured person. A better understanding could facilitate optimal rehabilitative planning. Objective . To explore patients' views on factors important to them in recovery following non-life threatening acute orthopaedic trauma. Methods . Descriptive study utilizing content analysis and chi-square analysis. To better understand recovery expectations, 168 adults who had sustained non-life threatening acute orthopaedic trauma were surveyed at 2, 12, and 26 weeks after injury and invited to respond to the following question "what are the most important things necessary for you to best recover?" Results . According to participant's responses, major themes on recovery involved a return to health and a return to health but with an ongoing plan, and for a minority (12%) recovery involved a focus on their current status. The study found that some recovery expectations changed over time. Conclusion . The journey to recovery is complex, often prolonged, and highly individual. Responses suggest that some injured persons need more assistance for a successful recovery than others. Those who appeared "caught in the moment" of the injury may benefit from clinical and rehabilitative management focusing on long-term recovery and acceptance of the injury event.